2021
DOI: 10.3171/case21433
|View full text |Cite
|
Sign up to set email alerts
|

Increase in clivo-axial angle is associated with clinical improvement in children undergoing occipitocervical fusion for complex Chiari malformation: patient series

Abstract: BACKGROUND The authors analyzed the pre- and postoperative morphometric properties of pediatric patients with complex Chiari malformation undergoing occipitocervical fusion (OCF) to assess clinical outcomes and morphometric properties that might influence postoperative outcomes. OBSERVATIONS The authors retrospectively reviewed 35 patients younger than 22 years with Chiari malformation who underwent posterior fossa decompression and OCF with or without endoscopic endonasal odontoidectomy at their institution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 17 publications
3
9
0
Order By: Relevance
“…We previously showed the association of short-term CT/MRI skull base morphometric changes after OCF with positive clinical outcomes in both adults and children. [ 9 , 18 ] This particular study extended those findings by examining the utility of X-ray morphometrics on preventing postoperative complications in complex CM patients undergoing PFD and OCF. Based on these observations, we described via case examples a novel method to use such predictive markers pre- and intraoperatively.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…We previously showed the association of short-term CT/MRI skull base morphometric changes after OCF with positive clinical outcomes in both adults and children. [ 9 , 18 ] This particular study extended those findings by examining the utility of X-ray morphometrics on preventing postoperative complications in complex CM patients undergoing PFD and OCF. Based on these observations, we described via case examples a novel method to use such predictive markers pre- and intraoperatively.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, CT and MRI are used to evaluate skull base morphometrics, such as the clivo-axial angle (CXA), that we have previously described. [ 9 , 18 ] Ventral compression due to restricted CSF space between the clivus and the upper cervical spine often results in an acute CXA and bulbar symptomology. [ 3 , 17 ] Our prior work, along with previous studies, demonstrated significant corrections to CXA in successful OCF cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This series included a patient with misrecognized basilar impression, which was the cause of the failure. Odontoidectomy has been recommended in the case of CM-1 with ventral compression [5,56]. It has been recommended to try reducing the basilar impression before removing the dens [57].…”
Section: Group 2b (Patients With Ineffective Fmd At Other Centers)mentioning
confidence: 99%
“…A growing body of literature suggests that chronic CCI manifests as a broad array of deleterious biomechanical effects upon the neural axis, in addition to causing altered cerebrospinal fluid and vascular flow [ 4 , 8 , 9 , 12 , 15 17 , 20 ]. Headaches, long tract findings, motor delay and quadriparesis, dyspraxia, gait instability, and altered autonomic function are recognized as consequences of chronic biomechanical deformation of structures at the craniocervical junction in many hereditary connective tissue disorders [ 8 , 13 , 16 , 19 , 21 25 ].…”
Section: Introductionmentioning
confidence: 99%